Geospatial Soil and Plant Tissue Analysis of Sericea Lespedeza (Lespedeza cuneata) Invasion around Lake Issaqueena, South Carolina. Issue 5 (8th March 2016) - Mikhailova, Elena; Hagan, Donald; Sharp, Julia; Allerton, Tristan; Burdette, Kylie; Mealing, Veeander; Ritter, Brian; Solomons, Allen; Stiglitz, Roxanne
ABSTRACT: This study was conducted to determine the chemical composition of sericea lespedeza ( Lespedeza cuneata ) as well as soil and landscape characteristics that correlate with its invasion. Geographic Information Systems (GIS) and Light Detection and Ranging (LiDAR) were used to determine the pattern of invasion and to quantify landscape metrics. Sericea lespedeza was distributed on both sides of the lake in Pacolet and Madison soil map units (Fine, kaolinitic, thermic Typic Kanhapludults) on average slopes of 17.5%. It was common along roads and trails with a preferred mean canopy cover of <50%. Plant tissue analysis revealed statistically higher concentrations of macronutrients nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg), calcium (Ca) and sulfur (S) and selected micronutrients in leaves compared to stems and roots. Micronutrients copper (Cu), manganese (Mn) and iron (Fe) were significantly higher in stems and roots. Soil analysis results showed no statistical difference between control and invaded plots for measured soil chemistry parameters.